Tinjauan Yuridis terhadap Pemasaran Kosmetik Ilegal secara Online di Indonesia - Febri Djaya (Journal of Judicial Review, 2020)
The writer’s purpose in conducting research on online marketed illegal cosmetics in Indonesia, in particular is to analyse and examine how the development of technology combined with the cosmetics industry is now growing because of the many individuals interested in cosmetics, especially women who want to beautify themselves with the aim of maximizing their self-confidence. This makes business actors often take advantage of their opportunities to produce and establish cosmetics businesses with the requirements given by the state. Business actor must have permission to produce, distribute and of course with the right quality standards, but in fact some business actors assume the requirements given are difficult and the process is time-consuming. Then the negative impacts arising from this matter is business actor or producer of production and distribution cosmetics has not tested products in laboratory, thus, it is fake and could be dangerous. Of course, this also has an impact on consumers who are exultant with illegal cosmetics and skincare products because they are tempted by massive promotions and discounts however it may cause people suffering losses due to illegal cosmetics offered in the market without correct information by cosmetic businesses. Act number 8 of 1999 concerning Consumer Protection can protect consumers victimized by producers or business actors producing and marketing illegal and irregular cosmetic products.